2022
DOI: 10.1111/dth.15534
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the efficacy of intralesional tranexamic acid versus platelet rich plasma in the treatment of melasma

Abstract: Melasma is a benign, acquired disorder of hyperpigmentation commonly affecting the face. Though easily diagnosable, a tangible treatment for melasma still remains elusive. Our aim was to compare the therapeutic efficacy and safety of tranexamic acid (TXA) and platelet rich plasma (PRP) microinjections in treating patients with melasma. In total, 40 patients with melasma (10 males, 30 females; age range: 21–54 years) were enrolled, and randomly assigned to one of the two groups consisting of 20 patients each. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…However, we found that younger patients (21–30 years) were more satisfied (statistically insignificant) with treatment with PRP + HQ as compared to their older counterpart. Similarly, Abdelshafy et at did not observe any correlation between age and degree of improvement 7 …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, we found that younger patients (21–30 years) were more satisfied (statistically insignificant) with treatment with PRP + HQ as compared to their older counterpart. Similarly, Abdelshafy et at did not observe any correlation between age and degree of improvement 7 …”
Section: Discussionmentioning
confidence: 87%
“…Emam et al 15 have demonstrated that PRP was equally effective in melasma when delivered by two different techniques: micro‐needling using dermapen (as in our study) versus micro‐injection using mesoneedles. Abdelshafy et at 7 . found a better improvement with intralesional PRP against intralesional Tranexamic acid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outro estudo abordou a comparação entre microinjeções e plasma rico em plaquetas (PRP). Ainda que a mesoterapia com PRP tenha se mostrado mais eficaz, os resultados não foram estatisticamente significativos, uma vez que ambos mostraram-se como opções terapêuticas eficazes(Patil & Bubna, 2022).…”
unclassified